Evaluate the following expression: (b^2)^3

(b^2)^3 = b^6

Question

Asked 2/15/2015 3:25:33 PM

Updated 2/15/2015 7:36:22 PM

1 Answer/Comment

Rating

3

(b^2)^3 = b^6

Added 2/15/2015 7:36:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [2/15/2015 8:25:25 PM]

what is heart in spanish **Weegy:** Do you have a question for Weegy? (More)

Question

Updated 2/15/2015 4:48:56 PM

1 Answer/Comment

Heart in Spanish is: el corazón.

Added 2/15/2015 4:48:30 PM

This answer has been confirmed as correct and helpful.

What is 4^-2 User: Find the quotient.
(4ab - 8a^2 + 12ac) ÷ 4a
**Weegy:** (4ab - 8a 2 + 12ac)/(4a) = [(4a)(b - 2a + 3c)]/(4a) = -2a + b + 3c **User:** Simplify the expression.
3(2y - 8) - 2y(5 - y)
**Weegy:** 3(2y - 8) - 2y(5 - y) = (6y - 24) - (10y - 2y^2) = 2y^2 - 4y - 24 **User:** Find the product.
(n + 7)(n - 2)
**User:** Find the quotient.
(6x^2 + 23x + 20) ÷ (5 + 2x)
**Weegy:** (6x^2 + 23x + 20) ÷ (5 + 2x) = 3x + 4 [(3x + 4)(2x + 5)]/(2x + 5) = 3x + 4 (More)

Question

Updated 2/17/2015 9:24:26 PM

2 Answers/Comments

evaluate and simplify the following expression (b^4)^2

Question

Updated 2/25/2015 3:17:20 AM

1 Answer/Comment

(b^4)^2

= b^8

= b^8

Added 2/25/2015 2:41:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [2/25/2015 3:17:16 AM]

Find the sum and choose the correct answer.
(-2u^3 + 5u - 1) + (7u^3 - 2u^2 + 9)

Question

Updated 2/20/2015 9:31:01 PM

1 Answer/Comment

(-2u^3 + 5u - 1) + (7u^3 - 2u^2 + 9)

= 5u^3 - 2u^2 + 5u + 8

= 5u^3 - 2u^2 + 5u + 8

Added 2/20/2015 9:31:01 PM

This answer has been confirmed as correct and helpful.

29,318,259

questions answered

There are no comments.